Efficient biotransformation of sulfide in anaerobic sequencing batch reactor by composite microbial agent: performance optimization and microbial community analysis - Liu, Huan; Dai, Luyao; Yao, Jiachao; Mei, Yu; Hrynsphan, Dzmitry; Tatsiana, Savitskaya; Chen, Jun (Environmental science and pollution research international, 2021)
Sulfur-containing wastewater is very common as an industrial waste, yet a high-efficiency composite microbial agent for sulfur-containing wastewater treatment is still lacking. In this work, three novel and efficient desulfurizing bacteria were isolated from the sewage treatment tank of Zhejiang Satellite Energy Co., Ltd. They were identified as Brucella melitensis (S1), Ochrobactrum oryzae (S8), and Achromobacter xylosoxidans (S9). These three strains of bacteria were responsible for the oxidative metabolism of sodium sulfide via a similar polythionate pathway, which could be expressed as follows: S 2- →S 2 O 3 2- /S 0 →SO 3 2- →SO 4 2- . Activated carbon, wheat bran, and diatomite at 1:1:1 ratio are used as carriers to construct a composite microbial agent containing the three bacteria. The desulfurization efficiency of 95% was predicted by response surface methodology under the following optimum conditions: the dosage of the inoculum was 3 g/L, pH 7.86, and temperature of 39 °C. Additionally, the impact resistance was studied in the anaerobic sequencing batch reactor. The removal capacity of microbial agent reached 98%. High-throughput analysis showed that composite microbial agent increased bacterial evenness and diversity, and the relative abundance of Brucellaceae increased from 5.04 to 8.79% in the reactor. In the process of industrial wastewater transformation, the transformation rate of sulfide by composite microbial agent was maintained between 70 and 81%. The composite microbial agent had potential for the treatment of sulfur-containing wastewater.